Optimisation of laboratory arsenic analysis for groundwaters of West Bengal, India and possible water testing strategy - Kundu, A.; Majumder, S.; Biswas, A.; Bhowmick, S.; Pal, C.; Mukherjee, Abhijit; Majumder, M.; Chatterjee, D. (Taylor & Francis, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Regular monitoring of arsenic (As) in groundwater is crucial from public health perspectives as millions of people are suffering due to use of contaminated aquifer water for drinking purposes. The routine analyses, especially in developing nations, are mostly done in localised government/non-government laboratories with limited resources, having the target of analysing large number of samples in each run. Thus apart from analytical sensitivity, cost-effectiveness of the method and eco-friendliness of the experimental operation are key surreptitious factors. This demands optimisation of total As measurement methods and finding a method that gives ‘optimum benefit’ considering all these factors together. The present study therefore evaluates four common As (total) measurement methods [iodometric-colorimetric method, silver diethyl dithiocarbamate method, molybdenum blue method and hydride generation atomic absorption spectrophotometric (HG-AAS) method] practised in the Bengal Delta Plain, in view of their analytical sensitivity, related environmental hazard and experimental costs. It was found that the HG-AAS method is analytically more sensitive, whereas the iodometric-colorimetric method and the molybdenum blue method are better choices in terms of eco-friendliness and cost-effectiveness, respectively. However, when all three factors (analytical reliability, environmental hazard and cost) are considered simultaneously, the molybdenum blue method was found to be placed first in the ‘optimum performance rank’ list. It was also found that both environmental hazard and cost play a more crucial role than analytical reliability, although this is case specific and would differ from place to place around the globe. Finally based on the results, we have hypothesised a water testing strategy for developing countries such as India where the molybdenum blue method can be adapted as a screening method and later the HG-AAS method can be used to precisely identify the groundwater samples with As concentration below the WHO drinking water guideline value of 10 µg/L.